Using Visual Scaffolding Strategy for Teaching Reading in Junior High School - Lestari, Nurul Fauziyah; Misdi, Misdi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2016)
This  research  was  aimed  to  investigate  the  effectiveness  of using  visualscaffolding strategy in teaching reading comprehension at the eighth grade of juniorhigh  school.  The  design  of  this  study  was  a  quasi  experimental  study.  The  subjectswere the students of state junior high schools in Cirebon, Indonesia. The data wereobtained  by  administering  reading  test  and  from  observation  as  a  supporting  dataanalysis.  The  data  of  the  test  were  analyzed  by  using t-test  formula  to  know  thedifference  of  the  students’  comprehension  in  reading  narrative  text  between  twogroups.  Meanwhile  the  result  of  the  observation  was  analyzed  descriptively.  Theresults  indicate  that  there  was a  significant  difference  on  students’  learning  resultbefore and after Visual Scaffolding applied.